PENGARUH PEMASARAN MEDIA SOSIAL, KEINOVATIFAN, DAN PERSONALISASI TERHADAP EKUITAS MEREK DENGAN KETERLIBATAN KONSUMEN SEBAGAI VARIABEL MEDIASI (Studi pada Konsumen Mie Sedaap) - Gunawan, Vanessa Cahyani; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT The FMCG products, particularly in food industry is one of the competitive fields. With Indonesia's continued growth, resilience and opportunities, many brands are competing in this sector. One of them is the brand Mie Sedaap. Based on a number of data, Mie Sedaap has never been the first choice for Indonesians in the instant noodle category. In addition, based on brief interviews with 10 Mie Sedaap customers, it was found that the loss of competition for Mie Sedaap occurred due to the lack of brand equity of Mie Sedaap compared to competitors, namely Indomie. The brief interview also revealed a number of factors that influence brand equity, namely social media marketing, innovativeness, personalization, and customer engagement. This study aims to investigate the factors that influence brand equity. With the quantitative research method, a sample of 105 questionnaire respondents with criteria had consumed Mie Sedaap and people aged 17-55 years who had seen Mie Sedaap social media campaigns or marketing. This data is then analyzed with SEM-PLS with SmartPLS application version 4. The results showed a positive and significant relationship between innovativeness and personalization with customer engagement, but social media marketing had an insignificant relationship with customer engagement. Where, personalization with flexibility indicators has the most powerful role in influencing customer engagement. Furthermore, customer engagement has a positive and significant influence on brand equity.